Angpt2/Tie2 autostimulatory loop controls tumorigenesis. Issue 5 (10th March 2022) - Karabid, Ninelia Minaskan; Wiedemann, Tobias; Gulde, Sebastian; Mohr, Hermine; Segaran, Renu Chandra; Geppert, Julia; Rohm, Maria; Vitale, Giovanni; Gaudenzi, Germano; Dicitore, Alessandra; Ankerst, Donna Pauler; Chen, Yiyao; et al.
Abstract: Invasive nonfunctioning (NF) pituitary neuroendocrine tumors (PitNETs) are non‐resectable neoplasms associated with frequent relapses and significant comorbidities. As the current therapies of NF‐PitNETs often fail, new therapeutic targets are needed. The observation that circulating angiopoietin‐2 (ANGPT2) is elevated in patients with NF‐PitNET and correlates with tumor aggressiveness prompted us to investigate the ANGPT2/TIE2 axis in NF‐PitNETs in the GH3 PitNET cell line, primary human NF‐PitNET cells, xenografts in zebrafish and mice, and in MENX rats, the only autochthonous NF‐PitNET model. We show that PitNET cells express a functional TIE2 receptor and secrete bioactive ANGPT2, which promotes, besides angiogenesis, tumor cell growth in an autocrine and paracrine fashion. ANGPT2 stimulation of TIE2 in tumor cells activates downstream cell proliferation signals, as previously demonstrated in endothelial cells (ECs). Tie2 gene deletion blunts PitNETs growth in xenograft models, and pharmacological inhibition of Angpt2/Tie2 signaling antagonizes PitNETs in primary cell cultures, tumor xenografts in mice, and in MENX rats. Thus, the ANGPT2/TIE2 axis provides an exploitable therapeutic target in NF‐PitNETs and possibly in other tumors expressing ANGPT2/TIE2. The ability of tumor cells to coopt angiogenic signals classically viewed as EC‐specific expands our view on the microenvironmental cues that are essential for tumor progression. Synopsis: There is currently no treatment for nonfunctioning pituitary neuroendocrine tumors (NF‐PitNETs), which are intracranial tumors associated with frequent relapse and severe comorbidities. This study establishes the ANGPT2/Tie2 signaling axis as a novel therapeutic target for NF‐PitNETs. Circulating ANGPT2 levels were elevated in NF‐PitNET patients and correlated with tumor proliferation rate, an indicator of tumor aggressiveness. Bioactive ANGPT2 was expressed and secreted by NF‐PitNET cells, and promoted angiogenesis and tumor cell growth in an autocrine and paracrine fashion. Functional TIE2 receptor was expressed by NF‐PitNET cells, and was directly activated by angiopoietins. PitNET cell growth was suppressed upon TIE2 knockout in mouse xenografts in vivo . ANGPT2/TIE2 pharmacological inhibition reduced the growth of NF‐PitNET primary tumor cells in vitro, as well as tumor xenografts and autochthonous NF‐PitNETs in MENX rats. Abstract : There is currently no treatment for nonfunctioning pituitary neuroendocrine tumors (NF‐PitNETs), which are intracranial tumors associated with frequent relapse and severe comorbidities. This study establishes the ANGPT2/Tie2 signaling axis as a novel therapeutic target for NF‐PitNETs.